Dampak workaholic parents terhadap perkembangan moral anak - Siti Adawiyah; Uus Kusnadi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
Workaholic Parent is a condition where both parents prioritize their work. Indeed, the work is also done to meet the needs of children and families. But besides, that there is something to note is the development of children. A child does not only need satisfaction in the financial field alone. But a child needs attention and encouragement, especially from a mother figure. In this study, the authors will explore the impact of workaholic parents on the moral development of children. In Indonesia today it becomes a problem that must be addressed immediately so that the nation's next generation is not morally deteriorated. In this study, the authors used quality methods or journal reviews. The source that the author took comes from an article, in a trusted journal It is true that work is a priority among the community. However, it must be evaluated immediately through parenting activities for parents about the urgency of love and attention that parents should give to their children. in addition, there needs to be planting awareness that there needs to be a quality time selection to be given to children. In such a way, it is expected that the level of satisfaction felt by the child to spend time with parents so that at the time of moral development process can be passed well.